A micro‐temporal geospatial analysis of medical marijuana dispensaries and crime in Long Beach, California. (18th February 2016) - Freisthler, Bridget; Ponicki, William R.; Gaidus, Andrew; Gruenewald, Paul J.
Abstract: Aims: To determine whether the density of marijuana dispensaries in California, USA, in 2012–13 was related to violent and property crimes, both locally and in adjacent areas, during a time in which local law enforcement conducted operations to reduce the number of storefront medical marijuana dispensaries. Design: Data on locations of crimes and medical marijuana dispensaries as well as other covariates were collected for a sample of 333 Census block groups. Setting: Long Beach, California, USA from January 2012 to December 2013. Observations: A total of 7992 space–time observations (from 333 Census block groups over 24 time‐points). Measurements: Outcome measures focused on block‐group counts of violent and property crimes. Predictors were numbers of local and adjacent‐area medical marijuana dispensaries. Covariates included markers of alcohol availability as well as area demographic and economic characteristics. Findings: After adjustment for covariates, density of medical marijuana dispensaries was unrelated to property and violent crimes in local areas but related positively to crime in spatially adjacent areas [incident rate ratio (IRR) = 1.0248, CI (1.0097, 1.0402) for violent crime, IRR = 1.0169, CI (1.0071, 1.0268) for property crime]. Conclusions: Using law enforcement to reduce medical marijuana dispensaries in California appears to have reduced crime in residential areas near to, but not in, these locations.